(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Water is one of the important ingredients of concrete and most used material in construction practices. As the discharge of grey water within the urban areas is huge, the possibility of its reuse in construction industry is investigated. This paper states the study of grey water treatment using some part of construction debris and reutilizing the treated grey water in production of concrete. Concrete mix of M20 grade was used. Compressive strength test, flexural strength, split tensile strength tests were done in order to study the properties of concrete made by using treated grey water. Comparison was done between results of concrete made using treated grey water to that of concrete made using tap water.